(untitled) (Stato, Chiese e pluralismo confessionale, 2020)
SOMMARIO: 1. La decretazione senza legge sul coronavirus - 2. Le disposizioni sulla libertà di culto - 3. Il limite della tutela della salute e l’inconferenza delle discipline pattizie - 4. Il bilanciamento delle specifiche misure - 5. Il rapporto laico tra Stato e confessioni religiose: un’icona. The freedom of worship in coronavirus times ABSTRACT: The state of emergency by coronavirus drove the italian government to legislate by means of decrees without law, that provided strong limits to constitutional rights as, among others, the freedom of worship. Particularly they banned masses coram populo in the churches and on occasion of funeral service in order to safeguard the health care. This paper aims to demonstrate that the Concordat beetween State and Church, well as the accords with other fellowships, is another matter with regard to a higher collective interest, constitutionally protected, like the halth care. The paper points out, moreover, how the adopted measures are reasonable and proportionate and, finally, the new leadership, respecting the secular order, held in this aspect by the italian Church, following the prints of pope Francis.